Solid pseudopapillary neoplasm of the pancreas: a retrospective study of 195 cases - Fu, Chang; Li, Xiaocong; Wang, Yongxin; Wang, Chuangshi; Jin, Hengwei; Liu, Kai; Xu, Hongji (Frontiers in Oncology, 2024)
Objective: Solid pseudopapillary neoplasm of the pancreas (SPN) is a rare exocrine tumor of the pancreas. The aim of our study is to summarize the clinical features of SPN and to analyze the risk factors for malignant SPN. Methods: From May 2013 to September 2022, patients who were pathologically confirmed to have SPN were retrospectively reviewed. Demographic data, clinical and pathological features, follow-up data were collected and analyzed. To investigate the factors influencing the benign or malignant nature of SPN, we employed logistic regression. Additionally, we utilized Kaplan-Meier curves to depict and analyze the patients' overall prognosis.Results: A total of 195 patients were included, 163 of whom were female and the average age of all patients was 31.7 years old. Among 195 patients, 101 patients (51.8%) had no obvious clinical symptoms and their pancreatic lesions were detected during routine examination. The primary symptom was abdominal pain and distension in 64 cases (32.8%). The maximum diameter of SPN tumors ranged from 1-17 cm (mean 6.19 cm). Forty-eight postoperative complications developed in 43 (22.1%) patients. After a median follow-up duration of 44.5 months, the overall 5-year survival rate was 98.8% and the recurrence rate was 1.5%. Furthermore, we observed a statistically significant difference in the completeness of the tumor capsule between benign and malignant SPN.Conclusion: SPN is associated with a favorable long-term survival after surgery in our large sample size cohort. For malignant SPN, tumor capsule incompleteness is an independent risk factor.